Curable artificial nail composition
The curable artificial nail composition addresses peeling and chipping issues by using (meth)acrylate oligomers and other specific components, achieving enhanced adhesion, water resistance, and antiseptic alcohol resistance, ensuring durable and clear nail coatings.
Patent Information
- Application Number
- JP2023096018
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
AI Technical Summary
Existing curable artificial nail compositions suffer from issues such as peeling, chipping, reduced adhesion due to water or disinfectant exposure, and clouding when in contact with water, failing to provide adequate durability and resistance.
A curable artificial nail composition comprising specific components like (meth)acrylate oligomers, (meth)acrylic acid, 2-hydroxybutyl(meth)acrylate, and trifunctional or higher functional (meth)acrylate compounds, along with a polymerization initiator, to enhance adhesion, water resistance, and antiseptic alcohol resistance.
The composition forms a cured coating film with excellent adhesiveness, water-resistant adhesiveness, and antiseptic alcohol-resistant adhesiveness, maintaining integrity and preventing clouding under wet conditions.
Smart Images

Figure 2024177722000001 
Figure 2024177722000002 
Figure 2024177722000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable artificial nail composition. [Background technology]
[0002] Nail art, which involves decorating natural nails on the hands and feet or gluing artificial nails and then decorating them, is becoming increasingly popular. In addition, artificial nails are formed on top of the nails to reinforce them and prevent them from cracking or peeling off due to external forces. For such nail decoration or reinforcement, resin-containing materials, so-called manicures, pedicures, and sculptures, are applied to the nails.
[0003] Recently, a photocurable artificial nail composition called gel nail has been attracting attention as a material used for decorating or reinforcing nails. Gel nail is a photocurable gel-like nail coating material (photocurable artificial nail composition), and is known to contain, for example, a (meth)acrylate oligomer and a (meth)acrylic monomer. Gel nail is applied to the nail and cured by irradiating with ultraviolet light, forming a crosslinked polymer coating by radical polymerization reaction, which is said to form a tough coating that is difficult to peel off from the nail. A widely known gel nail is composed of three layers: a base coat layer applied on the nail, a color coat layer applied between the base coat layer and the top coat layer, and a top coat layer applied on the outermost surface.
[0004] Curable artificial nail compositions such as gel nails have been developed to satisfy requirements such as adhesion of the cured coating film to a substrate (adhesive strength to the nail), adhesion duration, curability, aesthetic appearance of the cured coating film, etc. The adhesion (adhesive strength to the nail) and adhesion duration of the cured coating film of a curable artificial nail composition to a substrate immediately after application have become practical. However, when water or rubbing alcohol adheres to the cured coating film of the curable artificial nail composition during hand washing or hand disinfection in daily life, the adhesion of the cured coating film to the substrate (adhesive strength to the nail) and adhesion durability may decrease, resulting in peeling, etc. Furthermore, when exposed to water for a long period of time during housework, bathing, etc., the cured coating film may become cloudy.
[0005] Patent Document 1 discloses an artificial nail compound that includes (a) a compound having at least one radically polymerizable unsaturated double bond in the molecule, (b) an acidic phosphorus compound having at least one radically polymerizable unsaturated double bond in the molecule, and (c) a radical polymerization initiator. Patent Document 2 discloses an artificial nail composition comprising (a) a photopolymerizable monomer having at least one primary alcoholic hydroxyl group in the molecule, (b) a photopolymerizable monomer having at least one carboxyl group in the molecule, (c) a photopolymerizable monomer, and (d) a photopolymerization initiator. Patent Document 3 discloses a photocurable composition for nails or artificial nails, comprising: component (A): a urethane-modified (meth)acrylic oligomer; component (B): a (meth)acrylamide monomer; component (C): a (meth)acrylic monomer having an acidic group; and component (D): a photoinitiator. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2010-053097 A [Patent Document 2] JP 2014-23590 A [Patent Document 3] International Publication No. 2017 / 082058 Summary of the Invention [Problem to be solved by the invention]
[0007] The curable artificial nail compositions described in Patent Documents 1 to 3 are said to be capable of forming a cured coating film with excellent adhesion to human nails, but peeling or chipping may occur during use, requiring gel nail treatment to be performed again in a short period of time, and the adhesiveness to nails is still unsatisfactory. In addition, when washing hands or disinfecting hands in daily life, if water or disinfectant alcohol (ethanol for disinfecting hands) adheres to the cured coating film of the curable artificial nail composition, the adhesion of the cured coating film to the substrate (adhesive strength to the nail) and the durability of adhesion may decrease, causing peeling, etc. Furthermore, when exposed to water for a long time during housework, bathing, etc., the cured coating film may become cloudy, which is still unsatisfactory.
[0008] The problem to be solved by the present invention is to provide a curable artificial nail composition that is excellent in adhesion, water-resistant adhesion, and rubbing alcohol-resistant adhesion, and is capable of forming a cured coating film that is excellent in resistance to cloudiness upon immersion in water. [Means for solving the problem]
[0009] Means for Solving the Problems The present inventors have conducted extensive research to find that the above problems can be solved by providing a curable artificial nail composition having a specific composition, and have thus completed the present invention. Specifically, the following are included: [Section 1] (A) a (meth)acrylate oligomer, (B) (meth)acrylic acid, (C) Below (Ca)~(Cc); (Ca) 2-hydroxybutyl (meth)acrylate, (Cb) a (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule, (Cc) a (meth)acrylate mixture containing a trifunctional or higher polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate, wherein the content of the trifunctional or higher polyfunctional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less relative to 100% by mass of the total amount of the curable artificial nail composition; A (meth)acrylate component comprising one or more selected from the group consisting of: (D) a polymerization initiator, A curable artificial nail composition comprising: [Section 2] Item 2. The curable artificial nail composition according to item 1, further comprising (E) an alicyclic (meth)acrylate compound. [Section 3] Item 3. The curable artificial nail composition according to item 1 or 2, wherein the (A) (meth)acrylate oligomer is a polycarbonate polyurethane (meth)acrylate oligomer and / or a polyether polyurethane (meth)acrylate oligomer. Effect of the Invention
[0010] The present invention provides a curable artificial nail composition that is capable of forming a cured coating film that is excellent in adhesion, water-resistant adhesion, and rubbing alcohol resistance, and that is excellent in resistance to cloudiness upon immersion in water.
[0011] Although the mechanism and the like are unclear, the present inventors speculate on the effects of the present invention as follows: It should be noted, however, that the present invention is not limited to this speculation.
[0012] Since (meth)acrylic acid has a carboxyl group in the molecule, it is presumed that the adhesive strength of the cured coating film to the substrate can be chemically improved, making it possible to form a cured coating film with excellent adhesiveness. (Meth)acrylic acid has a higher ratio of vinyl groups per unit molecular weight than other monomers, and can increase the number of vinyl groups (reaction points) in the system. Furthermore, the addition of (meth)acrylic acid can improve the curability of the curable artificial nail composition. This is presumably because it makes it difficult for water molecules and ethanol molecules to enter the molecules of the cured coating film, improving water-resistant adhesion, water-immersion-resistant cloudiness, and rubbing alcohol-resistant adhesion.
[0013] (Ca) 2-hydroxybutyl methacrylate in the (C) (meth)acrylate component is presumed to behave hydrophobically compared to other hydroxyl group monomers due to its long alkyl chain. Therefore, it is presumed that the use of (Ca) 2-hydroxybutyl methacrylate improves resistance to water and rubbing alcohol, and even if these substances adhere to the cured coating film, swelling of the cured coating film can be suppressed, and the adhesive strength of the cured coating film will not decrease.
[0014] Regarding the cured coating film obtained from (C) a (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule (Cb) in the (meth)acrylate component (C) (e.g., THFMA (tetrahydrofurfuryl methacrylate) or MEDOYMA (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methacrylate), the inventors have found from the results of tensile tests that although the strain rate is large and the flexibility is high, the yield point is small and the film easily deforms. From this, it is presumed that the cured coating film has good conformability to the substrate (nail), but cannot be expected to have high adhesive strength because it undergoes irreversible deformation upon slight external impact. On the other hand, when (meth)acrylic acid is blended into the curable artificial nail composition, the effects of the individual components are exerted synergistically, the peel-off load in the 90° peel-off test can be increased, and the adhesive strength of the cured coating film to the substrate is improved. This is presumably what provides the adhesiveness that can withstand deformation of the cured coating film due to external impact, etc.
[0015] In the (Cc) (meth)acrylate mixture in the (C) (meth)acrylate component, the trifunctional or higher polyfunctional (meth)acrylate compound improves the crosslink density of the cured coating film. This makes it difficult for water molecules and ethanol molecules to enter the molecules of the cured coating film, and the cured coating film is less likely to swell, which is presumably why water-resistant adhesion, water-immersion-resistant cloudiness, and rubbing alcohol-resistant adhesion can be improved. On the other hand, when a trifunctional or more polyfunctional (meth)acrylate compound is used in a large amount, the cured coating film becomes too hard and is prone to brittle fracture. For this reason, 2-hydroxyethyl (meth)acrylate, which has high polarity and exhibits the property of improving and maintaining adhesive strength by strongly interacting with the substrate, and can reduce the hardness of the cured coating film, is used in combination, and further, (Cc) a (meth)acrylate mixture is used so that the content of the trifunctional or more polyfunctional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less based on 100% by mass of the total amount of the curable artificial nail composition. It is presumed that this allows the formation of a cured coating film of the curable artificial nail composition with a good balance between crosslink density, hardness, adhesiveness, and resistance to brittle fracture. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The curable artificial nail composition of the present invention will now be described. In this specification, the term "(meth)acrylate oligomer" refers to an acrylate oligomer and a methacrylate oligomer, and the term "(meth)acrylate monomer" refers to an acrylate monomer and a methacrylate monomer.
[0017] [(A) (Meth)acrylate Oligomer] The (A) (meth)acrylate oligomer is not particularly limited as long as it is an oligomer having one or more (meth)acryloyl groups in the molecule and having a plurality of one or more types of repeating units. The number of (meth)acryloyl groups contained in one molecule is not particularly limited, but is 1 to 10, preferably 2 to 8, from the viewpoint of the curability of the curable artificial nail composition and the hardness of the cured coating film. The number of (meth)acryloyl groups can be confirmed by analysis using infrared absorption spectroscopy (IR), nuclear magnetic resonance (NMR), gas chromatography mass spectrometry (GC / MS), etc. The weight-average molecular weight of the (meth)acrylate oligomer is not particularly limited. For example, it is 1,000 or more, preferably 2,000 or more, more preferably 3,000 or more, and for example, it is 100,000 or less, preferably 50,000 or less, more preferably 35,000 or less. By setting the weight-average molecular weight in this range, it is possible to improve the durability of the cured coating film while maintaining a low viscosity. The (meth)acrylate oligomer may be either a commercially available product or a synthetic product.
[0018] The (meth)acrylate oligomer is not particularly limited, and examples thereof include (i) (meth)acrylate oligomers having in their main skeleton (main chain) one or more types selected from the group consisting of a urethane bond, a bond generated by a ring-opening reaction of an epoxy group, an ester bond, an ether bond, a urea bond, a carbonate bond, and an amide bond; and (ii) (meth)acrylate oligomers having in their main skeleton (main chain) a molecular chain formed by polymerization of one or more types of monomers selected from the group consisting of styrene-based, (meth)acrylic-based, olefin-based, and diene-based monomers. Among these, the use of one or more types selected from the group consisting of urethane (meth)acrylate oligomers ((meth)acrylate oligomers having a urethane bond in the main skeleton), epoxy (meth)acrylate oligomers having a molecular chain generated by a ring-opening reaction of an epoxy group, ester (meth)acrylate oligomers ((meth)acrylate oligomers having an ester bond in the main skeleton), and ether (meth)acrylate oligomers ((meth)acrylate oligomers having an ether bond in the main skeleton) is advantageous in terms of adhesion, etc.
[0019] The urethane (meth)acrylate oligomer can be synthesized, for example, by reacting a polyol with a polyisocyanate to form an isocyanate group- or hydroxyl group-containing urethane prepolymer, and then reacting the isocyanate group- or hydroxyl group-containing urethane prepolymer with a compound having an active hydrogen-containing group and a (meth)acryloyl group in the molecule (hydroxyalkyl (meth)acrylate, (meth)acrylic acid, etc.) or a compound having an isocyanate group and a (meth)acryloyl group in the molecule, but the synthesis method is not limited to this method.
[0020] When a urethane (meth)acrylate oligomer is used in a curable artificial nail composition, a cured coating film having excellent elasticity, adhesion, and strength can be obtained. The one or more urethane (meth)acrylate oligomers usable in the present invention can be selected from those having one or more skeletons selected from the group consisting of polyether skeleton, polycarbonate skeleton, polyester skeleton, acrylic skeleton, and polyolefin skeleton. Among them, one or more polyether-based urethane (meth)acrylate oligomers having a polyether skeleton and / or polycarbonate-based urethane (meth)acrylate oligomers having a polycarbonate skeleton are preferred.
[0021] For example, a polyether-based urethane (meth)acrylate oligomer having one or more types of polyether skeleton can be obtained by adding a (meth)acrylic compound having a hydroxyl group, such as hydroxyethyl (meth)acrylate, to an isocyanate group-containing polyether urethane prepolymer obtained by reacting a polyoxyalkylene polyol, such as polyoxypropylene polyol, with a polyisocyanate, such as isophorone diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, or an isocyanurate or biuret product thereof, and subjecting 10% or more of the total number of isocyanate groups in the urethane prepolymer to an addition reaction with the (meth)acrylic compound having a hydroxyl group.
[0022] For example, a polycarbonate-based urethane (meth)acrylate oligomer having one or more types of polycarbonate skeleton can be obtained, like a polyether-based urethane (meth)acrylate oligomer, by adding a (meth)acrylic compound having a hydroxyl group, such as hydroxyethyl (meth)acrylate, to an isocyanate group-containing polycarbonate urethane prepolymer obtained by reacting a polycarbonate polyol with a polyisocyanate, and then subjecting 10% or more of the total number of isocyanate groups in the urethane prepolymer to an addition reaction with the (meth)acrylic compound having a hydroxyl group.
[0023] The urethane (meth)acrylate oligomer may be a commercially available product. Examples of commercially available products include, but are not limited to, one or more selected from the group consisting of AH-600, AT-600, UA-306H, UF-8001G (manufactured by Kyoeisha Chemical Co., Ltd.), RUA-071, RUA-003VE, RUA-075, RUA-048 (manufactured by Asia Chemical Industries Co., Ltd.), SUA TH1, SUA TH2, SUA-16N (manufactured by KSM Corporation), UV-3310B (manufactured by Mitsubishi Chemical Corporation), Art Resin UN-6303, UN-6304, UN-6305, UN-9000PEP, UN-9200A, UN-353, UN-333, UN-352 (manufactured by Negami Chemical Industries Co., Ltd.), AU-2040 (manufactured by Tokushiki Co., Ltd.), and KUA-PC2I (manufactured by KSM Corporation).
[0024] An epoxy (meth)acrylate oligomer having a molecular chain generated by a ring-opening reaction of an epoxy group can be synthesized, for example, by reacting a polyfunctional epoxy resin with a (meth)acrylate having a functional group reactive with an epoxy group, but is not limited to this method. Examples of commercially available products include, but are not limited to, one or more selected from the group consisting of EBECRYL 1259, 605, 1606 (manufactured by Daicel-Cytec), EPOXY ESTER 3000A, 3000MK, 3002A(N), 3002M(N), 40EM (manufactured by Kyoeisha Chemical Co., Ltd.).
[0025] An ester (meth)acrylate oligomer having an ester bond can be synthesized, for example, by adding a compound having a hydroxyl group and a (meth)acryloyl group in the molecule and / or (meth)acrylic acid or an acrylic compound having a carboxyl group to a carboxyl group and / or a hydroxyl group of an ester oligomer obtained by reacting a polyol with a polyvalent carboxylic acid, but is not limited to this method. Examples of commercially available products include, but are not limited to, one or more types selected from the group consisting of Aronix (registered trademark) M-6100, M-6200, M-6250, M-6500, M-7100, M-7300K, M-8030, M-8060, M-8100, M-8530, M-8560, and M-9050 (manufactured by Toagosei Co., Ltd.), and UV-3500BA, UV3520TL, UV-3200B, and UV-3000B (manufactured by Mitsubishi Chemical Corporation).
[0026] An ether (meth)acrylate oligomer having an ether bond can be synthesized, for example, by adding one or more members selected from the group consisting of a compound having a hydroxyl group and a (meth)acryloyl group in the molecule, (meth)acrylic acid, and a compound having a carboxyl group and a (meth)acryloyl group in the molecule to a hydroxyl group of an aliphatic polyether polyol or a hydroxyl group of an aromatic polyether polyol made from a raw material such as bisphenol, but is not limited to this method. Examples of commercially available products include, but are not limited to, one or more selected from the group consisting of UV-6640B, UV-6100B, UV-3700B (manufactured by Mitsubishi Chemical Corporation), Light Acrylate (registered trademark) 3EG-A, 4EG-A, 9EG-A, 14EG-A, PTMGA-250, BP-4EA, BP-4PA, BP-10EA, Light Ester 4EG, 9EG, 14EG (manufactured by Kyoeisha Chemical Co., Ltd.), and EBECRYL (registered trademark) 3700 (manufactured by Daicel-Cytec Co., Ltd.).
[0027] In the present invention, from the viewpoint of the adhesiveness, adhesion, durability, etc. of the curable artificial nail composition and / or the cured coating film thereof, it is preferable that the composition contains a urethane (meth)acrylate oligomer having a weight average molecular weight of 5,000 or more and 40,000 or less, in particular a polycarbonate polyurethane (meth)acrylate oligomer and / or a polyether polyurethane (meth)acrylate oligomer.
[0028] In the curable artificial nail composition of the present invention, the content of the (A) (meth)acrylate oligomer is not particularly limited. It may be, for example, 30.0% by mass or more, preferably 35.0% by mass or more, more preferably 40.0% by mass or more, and for example, 70.0% by mass or less, preferably 60.0% by mass or less, more preferably 55.0% by mass or less, based on 100% by mass of the total amount of the curable artificial nail composition. If the content of the (A) (meth)acrylate oligomer exceeds 70.0% by mass based on 100% by mass of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may become too high, and the applicability may decrease. If the content of the (A) (meth)acrylate oligomer is less than 30.0% by mass based on 100% by mass of the total amount of the curable artificial nail composition, the viscosity of the cured coating film of the curable artificial nail composition may be too low, and the applicability may decrease, and the cured coating film may become too hard and brittle.
[0029] [(B) (Meth)acrylic acid] The (B) (meth)acrylic acid, which is a component of the curable artificial nail composition of the present invention, may be at least one of acrylic acid and methacrylic acid. By including (B) (meth)acrylic acid, the adhesive strength of the cured coating film of the curable artificial nail composition to the nail or the underlying layer can be improved.
[0030] In the curable artificial nail composition of the present invention, the content of (B) (meth)acrylic acid is not particularly limited. For example, it is 0.0001% by mass or more, preferably 0.0005% by mass or more, more preferably 0.001% by mass or more, and for example, 10.0% by mass or less, preferably 8.0% by mass or less, more preferably 6.0% by mass or less, based on 100% by mass of the total amount of the curable artificial nail composition. If the content of (B) (meth)acrylic acid exceeds 10.0% by mass based on 100% by mass of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may become too low, which may reduce the applicability, and the cured coating film may easily fade, and the cured coating film may easily hydrolyze. If the content of (B) (meth)acrylic acid is less than 0.001% by mass based on 100% by mass of the total amount of the curable artificial nail composition, the adhesive strength of the cured coating film of the curable artificial nail composition to the nail or the lower layer may not be improved.
[0031] [(C) (Meth)acrylate Component] (C) The (meth)acrylate component includes the following (Ca) to (Cc); (Ca) 2-hydroxybutyl (meth)acrylate, (Cb) a (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule, (Cc) a (meth)acrylate mixture containing a trifunctional or higher polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate, wherein the content of the trifunctional or higher polyfunctional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less relative to 100% by mass of the total amount of the curable artificial nail composition; The present invention includes one or more types selected from the group consisting of:
[0032] <(Ca) 2-Hydroxybutyl (meth)acrylate> The 2-hydroxybutyl (meth)acrylate (Ca) that may be contained in the (meth)acrylate component (C), which is a constituent of the curable artificial nail composition of the present invention, may be at least one of 2-hydroxybutyl acrylate and 2-hydroxybutyl methacrylate. By containing 2-hydroxybutyl (meth)acrylate (Ca), the cured coating film of the curable artificial nail composition has improved resistance to water and rubbing alcohol, and even if these substances adhere to the cured coating film, swelling of the cured coating film is suppressed, and the adhesive strength of the cured coating film can be maintained without being reduced.
[0033] In the curable artificial nail composition of the present invention, the content of (Ca) 2-hydroxybutyl (meth)acrylate is not particularly limited. For example, it is 5.0 mass% or more, preferably 10.0 mass% or more, more preferably 20.0 mass% or more, and for example, 50.0 mass% or less, preferably 45.0 mass% or less, more preferably 40.0 mass% or less, based on 100 mass% of the total amount of the curable artificial nail composition. If the content of (Ca) 2-hydroxybutyl (meth)acrylate exceeds 50.0 mass% based on 100 mass% of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may be too low, which may reduce the applicability, and the curing heat during curing may be high, which may cause the cured coating film to easily crack. If the content of (Ca) 2-hydroxybutyl (meth)acrylate is less than 5.0 mass% relative to 100 mass% of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may increase, resulting in poor applicability, and there is a risk that uncured components may remain on the surface of the cured coating film of the curable artificial nail composition.
[0034] <(Cb) (Meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule> The (meth)acrylate compound (Cb) having a (meth)acryloyloxy group and a heterocycle in the molecule which may be contained in the (meth)acrylate component (C), which is a constituent of the curable artificial nail composition of the present invention, is not particularly limited as long as it is a compound having one or more (meth)acryloyloxy groups (CH2=CHCOO- groups or CH2=C(CH3)COO- groups) and one or more heterocycles in the molecule. For example, glycidyl (meth)acrylate, 4-(meth)acryloyloxymethyl-2-cyclohexyl-1,3-dioxolane, (2-methyl-2-ethyl-1,3-dioxolane-4-yl)methyl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, (2-isobutyl-2-methyl-1,3-dioxolane-4-yl)methyl (meth)acrylate, (2-ethyl-2-methyl-1,3-dioxolane-4-yl)methyl (meth)acrylate, (1,4-dioxaspiro[4,5]decan-2-yl)methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tetrafurfuryl alcohol, Examples of the acrylate copolymer include one or more selected from the group consisting of aryl oligo(meth)acrylate, alkoxylated tetrahydrofurfuryl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (meth)acryloylmorpholine, N-(meth)acryloyloxyethylhexahydrophthalimide, pentamethylpiperidyl (meth)acrylate, isocyanuric acid di(meth)acrylate, isocyanuric acid tri(meth)acrylate, triazine tri(meth)acrylate, N-(meth)acryloxysuccinimide, and N-(meth)acryloxyphthalimide. By including a (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule (Cb), the flexibility of the cured coating film and its conformability to the substrate (nail) can be improved.
[0035] In the curable artificial nail composition of the present invention, the content of the (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule (Cb) is not particularly limited. For example, it is 5.0% by mass or more, preferably 10.0% by mass or more, more preferably 20.0% by mass or more, and for example, 50.0% by mass or less, preferably 45.0% by mass or less, more preferably 40.0% by mass or less, based on 100% by mass of the total amount of the curable artificial nail composition. If the content of the (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule (Cb) exceeds 50.0% by mass based on 100% by mass of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may be too low, which may reduce the applicability, and the curing heat during curing may be high, which may cause the cured coating film to easily crack. If the content of the (Cb) (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule is less than 5.0 mass% relative to 100 mass% of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may increase, resulting in poor applicability, and there is a risk that uncured components may remain on the surface of the cured coating film of the curable artificial nail composition.
[0036] <(Cc) Tri- or higher functional (meth)acrylate compound and (meth)acrylate mixture containing 2-hydroxyethyl (meth)acrylate> The (Cc) (meth)acrylate mixture containing a tri- or higher functional polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate that may be contained in the (C) (meth)acrylate component, which is a constituent of the curable artificial nail composition of the present invention, is not particularly limited as long as it contains a tri- or higher functional polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate, and the content of the tri- or higher functional polyfunctional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less with respect to 100% by mass of the total amount of the curable artificial nail composition.
[0037] Examples of the trifunctional or higher polyfunctional (meth)acrylate compound include one or more selected from the group consisting of tri(meth)acrylate monomers such as glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, and ε-caprolactone-modified tris(acryloxyethyl)isocyanurate; tetra(meth)acrylate monomers such as dipentaerythritol tetra(meth)acrylate; polypentaerythritol (meth)acrylates such as dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol (meth)acrylate, and tetrapentaerythritol (meth)acrylate; (meth)acrylate monomers having four or more (meth)acrylate groups such as ethoxylated isocyanuric acid triacrylate and ethoxylated pentaerythritol tetraacrylate; and the like. The 2-hydroxyethyl (meth)acrylate may be at least one of 2-hydroxyethyl acrylate or 2-hydroxyethyl methacrylate.
[0038] By including a trifunctional or higher polyfunctional (meth)acrylate compound, the crosslink density of the cured coating film can be improved, and water molecules and ethanol molecules can be made less likely to penetrate into the molecules of the cured coating film, thereby suppressing swelling of the cured coating film. On the other hand, by including 2-hydroxyethyl (meth)acrylate, the adhesive strength with the substrate can be improved and maintained, and the hardness of the cured coating film can be reduced. Thus, by using a trifunctional or higher polyfunctional (meth)acrylate compound in combination with 2-hydroxyethyl (meth)acrylate, and further by setting the content of the trifunctional or higher polyfunctional (meth)acrylate compound to 0.01% by mass or more and 5.0% by mass or less based on 100% by mass of the total amount of the curable artificial nail composition, a cured coating film of the curable artificial nail composition having a good balance of crosslink density, hardness, adhesiveness, and brittle fracture resistance can be formed.
[0039] In the curable artificial nail composition of the present invention, the content of (Cc) the (meth)acrylate mixture containing a tri- or higher functional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate is not particularly limited, so long as the content of the tri- or higher functional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less relative to 100% by mass of the total amount of the curable artificial nail composition. In addition, the content of 2-hydroxyethyl (meth)acrylate in the (meth)acrylate mixture containing (Cc) a trifunctional or higher polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate is not particularly limited. For example, the content of 2-hydroxyethyl (meth)acrylate is, for example, 5.0 mass% or more, preferably 10.0 mass% or more, more preferably 20.0 mass% or more, and for example, 50.0 mass% or less, preferably 45.0 mass% or less, more preferably 40.0 mass% or less, based on 100 mass% of the total amount of the curable artificial nail composition. If the content of 2-hydroxyethyl (meth)acrylate exceeds 50.0 mass% based on 100 mass% of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may be too low, which may reduce the applicability, and the curing heat during curing may be high, which may cause the cured coating film to easily crack. If the content of 2-hydroxyethyl (meth)acrylate is less than 5.0 mass% relative to 100 mass% of the total amount of the curable artificial nail composition, the viscosity of the curable artificial nail composition may increase, resulting in reduced applicability, and the adhesion of the cured coating film of the curable artificial nail composition may not be improved.
[0040] [(D) Polymerization initiator] The polymerization initiator (D), which is a component of the curable artificial nail composition of the present invention, is not particularly limited as long as it generates radicals when given energy by irradiation with light (e.g., ultraviolet light) or heat, and can initiate polymerization of the (A) (meth)acrylate oligomer, (B) (meth)acrylic acid, (C) (meth)acrylate component, and (E) alicyclic (meth)acrylate compound. For example, one or more polymerization initiators selected from the group consisting of acylphosphine oxides, α-hydroxyalkylphenones, benzoin ethers, benzyl ketals, acid esters, α-aminoalkylphenones, benzophenones, thioxanthones, titanocenes, quinones, peroxides, azos, and persulfates may be used. For example, when a photopolymerization initiator is used, good curability can be imparted to the curable artificial nail composition even when the composition is irradiated with light using various light sources including a UV-LED light source.
[0041] For example, an acylphosphine oxide-based polymerization initiator generates radicals when irradiated with ultraviolet light having a wavelength of 365 to 405 nm emitted from a commonly used UV-LED light source. Therefore, even when the composition is cured by irradiating light using various light sources including a UV-LED light source, the composition can be imparted with good curability. Furthermore, when the composition is cured by irradiating light using a UV-LED light source, yellowing of the cured coating film can be prevented. Examples of the acylphosphine oxide polymerization initiator include one or more selected from the group consisting of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, etc. In particular, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (OMNIRAD TPO) can be preferably used in the present invention since it also functions as a skin conditioning agent.
[0042] Examples of polymerization initiators other than acylphosphine oxide polymerization initiators include 1-hydroxy-cyclohexyl-phenyl-ketone (OMNIRAD 184), 1-(4-(phenylthio)-2,2-(O-benzoyloxime))1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]-phenyl}-2-methyl Propan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, thioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, 2-chlorothioxanthone, 1-chloro-4-propylthioxanthone, 3-[3,4-dimethyl-9-oxo-9H-thioxanthone-2-yl-oxy]-2-hydroxypropyl-N,N,N-trimethylammonium chloro lide, fluorothioxanthone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, oligo(2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propanone), 4-benzoyl-4'-methyl-diphenyl sulfide, 1,2-octanedione, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2 -Dimethylamino-1-(4-morpholinophenyl)-butanone-1,2,2-dimethoxy-1,2-diphenylethan-1-one,2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]phenyl}-2-methylpropane,isophthalphenone,methyl phenylglyoxylate,butylanthraquinone,ethylanthraquinone,phenanthrenequinone,camphorquinone,benzophenone,4-phenylbenzophenone,benzoylbenzoic acid,hydroxybenzophenone,4,4'-Bis(diethylamino)benzophenone, benzoin, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzoin isobutyl ether, benzil dimethyl ketal, 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 4-t-butyl-trichloroacetophenone, diethoxyacetophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2' -Azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyronitrile), 2,2'-azobis-2-methylbutyronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(methylisobutyrate), t-butyl hydroperoxide, cumene hydroperoxide, diacetyl peroxide, didecanoyl peroxide , di-t-butyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, dicumyl peroxide, di(3,5,5-trimethylhexanoyl) peroxide, 2,5-dimethylhexane-2,5-dihydroperoxide, dilauroyl peroxide, disuccinic acid peroxide, dibenzoyl peroxide, parachlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, t-butyl peroxypivalate, t-butyl peroxybenzoate, t-hexyl peroxide Side paroxysmal, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, n-butyl-4,4-di(t-butylperoxy)valerate, 1,1-di(t-butylperoxy)cyclohexane, 1,1-di(t-hexylperoxy)cyclohexane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,Examples of the peroxycarbonyl group include 1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, dicetyl peroxydicarbonate, t-hexylperoxyisopropyl monocarbonate, diisopropyl peroxydicarbonate, t-butylperoxyisopropyl carbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di(2-ethylhexyl)peroxydicarbonate, potassium persulfate, sodium persulfate, and ammonium persulfate.
[0043] In the curable artificial nail composition of the present invention, it is preferable to use a polymerization initiator capable of generating radicals and initiating polymerization at ultraviolet wavelengths of around 405 nm and around 365 nm irradiated during curing, and it is more preferable to use a polymerization initiator containing an acylphosphine oxide polymerization initiator. In addition to the acylphosphine oxide polymerization initiator, a polymerization initiator containing an α-hydroxyalkylphenone polymerization initiator may be used, and a polymerization initiator composition containing an acylphosphine oxide polymerization initiator and a peroxide polymerization initiator may also be used.
[0044] In the curable artificial nail composition of the present invention, the content of the polymerization initiator (D) is, for example, 0.05% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, relative to the total amount of the curable artificial nail composition (100% by mass), and is, for example, 15.0% by mass or less, preferably 12.0% by mass or less, and more preferably 10.0% by mass or less. If the content of the polymerization initiator (D) exceeds 15.0% by mass, the cured coating film of the curable artificial nail composition may become brittle or may turn yellow (yellowing). If the content of the polymerization initiator (D) is less than 0.05% by mass, the curing of the curable artificial nail composition may take a long time, and curing may be insufficient.
[0045] In the curable artificial nail composition of the present invention, when a polymerization initiator containing an acylphosphine oxide polymerization initiator and an α-hydroxyalkylphenone polymerization initiator is used as the (D) polymerization initiator, the content of the acylphosphine oxide polymerization initiator is, for example, 0.05% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and for example, 4.0% by mass or less, preferably 3.0% by mass or less, and more preferably 1.0% by mass or less, based on 100% by mass of the total amount of the curable artificial nail composition. The content of the α-hydroxyalkylphenone polymerization initiator is, for example, 1.0% by mass or more, preferably 2.0% by mass or more, more preferably 3.0% by mass or more, and for example, 15.0% by mass or less, preferably 12.0% by mass or less, and more preferably 10.0% by mass or less, based on 100% by mass of the total amount of the curable artificial nail composition. The total content of the acylphosphine oxide polymerization initiator and the α-hydroxyalkylphenone polymerization initiator is, for example, 1.05% by mass or more, preferably 2.0% by mass or more, more preferably 3.0% by mass or more, and even more preferably more than 4.0% by mass, and is, for example, 15.0% by mass or less, preferably 12.0% by mass or less, and more preferably 10.0% by mass or less. If the content of the acylphosphine oxide polymerization initiator exceeds 4.0% by mass, the cured coating film of the curable artificial nail composition may become brittle or may turn yellow (yellowing). If the content of the acylphosphine oxide polymerization initiator is less than 0.05% by mass, the curing heat of the curable artificial nail composition may become high, and the temperature rise during curing may become large.
[0046] [(E) Alicyclic (meth)acrylate compound] The curable artificial nail composition of the present invention may contain (E) an alicyclic (meth)acrylate compound as a constituent component. The (E) alicyclic (meth)acrylate compound is not particularly limited as long as it is a compound having one or more (meth)acryloyl groups and one or more types of alicyclic rings in the molecule. The number of (meth)acryloyl groups contained in one molecule is not particularly limited, but is 1 to 3, preferably 1 to 2, from the viewpoints of the curability of the curable artificial nail composition and the hardness of the cured coating film.
[0047] Examples of the (E) alicyclic (meth)acrylate compound include one or more selected from the group consisting of isobornyl (meth)acrylate, adamantyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc. Among these, one or more selected from the group consisting of isobornyl (meth)acrylate, adamantyl (meth)acrylate, and cyclohexyl (meth)acrylate are preferred, with isobornyl (meth)acrylate being particularly preferred.
[0048] In the curable artificial nail composition of the present invention, the content of the (E) alicyclic (meth)acrylate compound can be, for example, 30.0% by mass or less, preferably 25.0% by mass or less, based on 100% by mass of the total amount of the curable artificial nail composition. In the present invention, the content of the (E) alicyclic (meth)acrylate compound can be 0% by mass (not including the (E) alicyclic (meth)acrylate compound) based on 100% by mass of the total amount of the curable artificial nail composition, but can be, for example, 10% by mass or more, preferably 15% by mass or more.
[0049] [(F) Other ingredients] In addition to the above (A) to (E), various components can be blended as "(F) other components" in the curable artificial nail composition of the present invention within a range that does not adversely affect the storage stability, curability, color tone of the cured coating film, durability of the cured coating film, adhesion of the cured coating film, viscosity, handleability, coatability, etc. Examples of the (F) other components include one or more selected from the group consisting of various additives such as polymerization inhibitors, colorants, radically polymerizable compounds other than the above (A) to (C) and (E), polyol compounds, polyfunctional thiol compounds, mercaptoalkanoic acids, resins other than the above (A), solvents, fragrances, anti-settling agents such as alumina, silicone-based and fluorine-based antifoaming agents, silane coupling agents such as γ-glycidoxypropyltrimethoxysilane, polymerization accelerators such as tertiary amines, surface tension adjusters, flame retardants, antioxidants, ion adsorbents, stress reducers, preservatives, antibacterial agents, flexibility imparting agents, waxes, halogen traps, leveling agents, wetting improvers, and decorative materials.
[0050] Examples of the polymerization inhibitor include one or more selected from the group consisting of tocopherol compounds, quinone compounds, phenolic compounds, catechol compounds, oxydiphenylamine compounds, nitroso compounds, nitrone compounds, nitrile compounds, hydrazyl compounds, phenothiazine compounds, etc. The polymerization inhibitor may be contained in an amount of, for example, 1.0% by mass or less, preferably 0.7% by mass or less, based on the total amount of the curable artificial nail composition.
[0051] The colorant may be one or more selected from the group consisting of pigments, glittering materials, and dyes, and may be used in any amount to impart a desired color tone to the curable artificial nail composition. Also, as a bluing agent, it may be used to eliminate the yellow color of the curable artificial nail composition. In particular, it may be one or more selected from the group consisting of inorganic pigments, glittering materials, organic pigments, and dyes used in nail coating materials, and does not significantly inhibit curing by ultraviolet irradiation (light irradiation) or the like. The curable artificial nail composition before curing can contain not only pigments but also resin particles and decorative materials that can be incorporated into known curable artificial nail compositions.
[0052] Examples of colorants include Brown No. 201, Black No. 401, Purple No. 201, Purple No. 401, Blue No. 1, Blue No. 2, Blue No. 201, Blue No. 202, Blue No. 203, Blue No. 204, Blue No. 205, Blue No. 403, Blue No. 404, Green No. 201, Green No. 202, Green No. 204, Green No. 205, Green No. 3, Green No. 401, Green No. 402, Yellow No. 201, Yellow No. 202-(1), Yellow No. 20 No. 2-(2), Yellow No. 203, Yellow No. 204, Yellow No. 205, Yellow No. 4, Yellow No. 401, Yellow No. 402, Yellow No. 403-(1), Yellow No. 404, Yellow No. 405, Yellow No. 406, Orange 201 No., Orange No. 203, Orange No. 204, Orange No. 205, Orange No. 206, Orange No. 207, Orange No. 401, Orange No. 402, Orange No. 403, Red No. 102, Red No. 104-(1), Red No. 105-(1 ), Red 106, Red 2, Red 201, Red 202, Red 203, Red 204, Red 205, Red 206, Red 207, Red 208, Red 213, Red 214, Red 215, Red 218, Red 219, Red 220, Red 221, Red 223, Red 225, Red 226, Red 227, Red 228, Red 230-(1), Red 23 0-(2), Red No. 231, Red No. 232, Red No. 3, Red No. 401, Red No. 405, Red No. 501, Red No. 502, Red No. 503, Red No. 504, Red No. 505, Red No. 506, titanium oxide, iron oxide, chromium oxide, manganese violet, carbon black, metal powder, metal flakes, metal oxide flakes, glass flakes, and the like.
[0053] The radical polymerizable compound other than (A) to (C) and (E) is not particularly limited, and may be, for example, one or more selected from the group consisting of vinyl group-containing compounds, allyl group-containing compounds, and (meth)acrylate compounds other than (A) to (C) and (E). Examples of the vinyl group-containing compound include one or more selected from the group consisting of styrene, α-methylstyrene, vinyltoluene, vinylbenzoic acid, vinylphenol, α-chlorostyrene, vinyl acetate, vinyl propionate, methyl vinyl ether, ethyl vinyl ether, N-vinylpyrrolidone, vinylpyridine, and vinyl group-containing oligomers. The allyl group-containing compound may be, for example, one or more compounds selected from the group consisting of allyl glycidyl ether, triallyl cyanurate, allyl benzoate, and allyl group-containing oligomers.
[0054] Examples of the (meth)acrylate compounds other than (A) to (C) and (E) include compounds having one or more (meth)acryloyl groups in the molecule. The number of (meth)acryloyl groups in one molecule is not particularly limited, but is 1 to 10, preferably 1 to 8, and more preferably 1 to 6, from the viewpoints of the curability of the curable artificial nail composition and the hardness of the cured coating film.
[0055] Examples of the (meth)acrylate compound having one (meth)acryloyl group include Esters of monohydric alcohols such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate with (meth)acrylic acid; (meth)acrylates having a carboxyl group such as carboxyethyl (meth)acrylate, crotonic acid, maleic acid, fumaric acid, maleic acid monoalkyl esters, itaconic acid, and cinnamic acid; ammonium salts and metal salts of (meth)acrylate monomers having a carboxyl group; (meth)acrylates having an acid anhydride group such as maleic anhydride, itaconic anhydride, and citraconic anhydride; (meth)acrylamide, N-methyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide (meth)acryloyl group-containing amide compounds such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, etc.; nitrogen-containing alkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, Nt-butylaminoethyl (meth)acrylate, etc.; phosphate ester-based (meth)acrylates such as (meth)acryloyloxyethyl phosphate, (meth)acryloyloxypropyl phosphate, caprolactone-modified (meth)acryloyloxyethyl phosphate, (meth)acrylic acid ethyl hexanoate phosphate, and (meth)acrylic acid pentyl propanoate phosphate;Glycidyl (meth)acrylate, 4-(meth)acryloyloxymethyl-2-cyclohexyl-1,3-dioxolane, (2-methyl-2-ethyl-1,3-dioxolane-4-yl)methyl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, (2-isobutyl-2-methyl-1,3-dioxolane-4-yl)methyl (meth)acrylate, (2-ethyl-2-methyl-1,3-dioxolane-4-yl)methyl (meth)acrylate, (1,4-dioxaspiro[4,5]decan-2-yl)methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tetrafurfuryl alcohol oligo(meth)acrylate At least one selected from the group consisting of heterocyclic ring-containing (meth)acrylates such as alkoxylated tetrahydrofurfuryl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, (meth)acryloylmorpholine, N-(meth)acryloyloxyethylhexahydrophthalimide, pentamethylpiperidyl (meth)acrylate, isocyanuric acid di(meth)acrylate, isocyanuric acid tri(meth)acrylate, triazine tri(meth)acrylate, N-(meth)acryloxysuccinimide, and N-(meth)acryloxyphthalimide;
[0056] Examples of the (meth)acrylate compound having two or more (meth)acryloyl groups include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene di(meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, pentaerythritol di(meth)acrylate, di(meth)acryloyloxyethyl phosphate, di(meth)acryloyloxypropyl phosphate, caprolactone-modified di(meth)acryloyloxyethyl phosphate, di(meth)acrylic acid ethyl hexanoate, ... di(meth)acrylate monomers such as phosphate ester-based di(meth)acrylates, such as pentyl ester propanoate; tri(meth)acrylate monomers, such as glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, and ε-caprolactone-modified tris(acryloxyethyl)isocyanurate; tetra(meth)acrylate monomers, such as dipentaerythritol tetra(meth)acrylate and ethoxylated isocyanuric acid triacrylate; (Meth)acrylate monomers; (meth)acrylate monomers having four or more (meth)acrylate groups, such as dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol (meth)acrylate, polypentaerythritol (meth)acrylate, etc., and ethoxylated pentaerythritol tetraacrylate; and the like. In addition, when the curable artificial nail composition contains both a tri- or higher functional polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate, it is deemed to satisfy the requirement (Cc) above, and the content of the tri- or higher functional polyfunctional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less, relative to 100% by mass of the total amount of the curable artificial nail composition.
[0057] The polyol compound functions as a diluent and an adhesion improver for the curable artificial nail composition. Examples of the polyol compound include one or more selected from the group consisting of alkyl polyols, polyester polyols, polyether polyols, acrylic polyols, polybutadiene polyols, and phenolic polyols. Among them, alkyl polyols, polyester polyols, and polyether polyols are preferred. The alkyl polyol may be one or more selected from the group consisting of ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, neopentyl glycol, cyclohexanedimethanol, trimethylolpropane, pentaerythritol, and the like.
[0058] The polyester polyol may be one or more selected from the group consisting of condensation polyester polyol, addition polymerization polyester polyol, polycarbonate polyol, etc. The condensation polyester polyol may be obtained by a condensation reaction between one or more diol compounds selected from the group consisting of ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 1,4-hexanedimethanol, diol dimer acid, polyethylene glycol, etc., and one or more organic polybasic acids selected from the group consisting of adipic acid, isophthalic acid, terephthalic acid, sebacic acid, etc., and the molecular weight is preferably 100 to 100,000. The addition polymerization polyester polyol may be polycaprolactone, and the molecular weight is preferably 100 to 100,000. Polycarbonate polyol is synthesized by direct phosgenation of polyol, transesterification with diphenyl carbonate, or the like, and preferably has a molecular weight of 100 to 100,000. An example of the polyether polyol is a polyether polyol obtained by ring-opening polymerization of an alkylene oxide.
[0059] The polyfunctional thiol compound is not particularly limited as long as it has two or more thiol groups in the molecule. The polyfunctional thiol compound is blended as a chain transfer agent, a curing regulator, a crosslinking agent and a viscosity regulator of the curable artificial nail composition. For example, the compound having a thiol group or a group that reacts to become a thiol group can be obtained by reacting the hydroxyl group of a polyol compound such as trimethylolpropane, pentaerythritol, dipentaerythritol, or ethylene glycol with the thiol group. For example, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tristhioglycolate, trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakis thioglycolate, pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptobutyrate), 1,3,5-tris[2-(3-mercaptobutyryloxy)ethyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, tris[(3-mercaptopropionyloxy)ethyl]-isocyanurate, 1,4-bis(3-mercapto butyryloxy)butane, 1,2-ethanedithiol, 1,3-propanedithiol, 1,4-butanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,2-cyclohexanedithiol, decanedithiol, ethylene glycol bisthioglycolate, ethylene glycol bisthiopropionate, ethylene glycol bisthioglycolate (EGTG), 1,4-butanediol bisthiopropionate (BDTG), trimercaptopropionic acid tris(2-hydroxyethyl)isocyanurate, 1,4-dimethylmercaptobenzene, 2,4,6-trimercapto-s-triazine, 2-(N,N-dibutylamino)-4,6-dimercapto-s-triazine, and other polyfunctional thiol group-containing monomers can be mentioned.
[0060] The mercaptoalkanoic acid is not particularly limited as long as it is a compound having at least one thiol group and at least one carboxyl group in the molecule, and examples thereof include at least one of mercaptoacetic acid, 3-mercaptopropionic acid, 2-mercaptopropionic acid, 3-mercaptobutyric acid, 4-mercaptobutyric acid, 2-mercaptoisobutyric acid, 3-mercaptoisobutyric acid, 3-mercapto-3-methylbutyric acid, 2-mercaptovaleric acid, and 4-mercaptovaleric acid.
[0061] The resin is not particularly limited as long as it is neither polymerizable nor a polyol compound, and examples thereof include one or more selected from the group consisting of polyurethane resins, polyester resins, polyamide resins, polyether resins, olefin resins, aromatic olefin resins, aromatic hydrocarbon resins, acrylic resins, vinyl chloride resins, vinyl acetate resins, polyvinyl alcohol resins, polyvinyl acetal resins, core-shell polymers, graft resins, and block resins.
[0062] The solvent is not particularly limited as long as it can adjust the viscosity at the time of application by dilution. For example, one or more selected from the group consisting of alcohols such as methanol, ethanol, propanol, n-butanol, and i-butanol; ketones such as acetone, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone; cellosolves such as ethyl cellosolve; aromatic hydrocarbons such as toluene and xylene; glycol ethers such as propylene glycol monomethyl ether; acetates such as methyl acetate, ethyl acetate, and butyl acetate; and diacetone alcohol.
[0063] [Viscosity of Curable Artificial Nail Composition] The curable artificial nail composition of the present invention can have a viscosity at 25° C. of, for example, 0.1 Pa·s or more and 60.0 Pa·s or less. The viscosity is preferably 0.5 Pa·s or more, more preferably 0.7 Pa·s or more, and is preferably 50.0 Pa·s or less, more preferably 40.0 Pa·s or less. By setting the viscosity within such a range, a curable artificial nail composition that is excellent in applicability with an applicator such as a brush or inkjet can be obtained.
[0064] [Uses of the curable artificial nail composition] The curable artificial nail composition of the present invention is a composition for coating the surface of the nail, like common manicures and pedicures. The curable artificial nail composition of the present invention has excellent leveling properties and is therefore capable of forming a smooth cured coating film. The cured coating film has appropriate hardness and therefore is less susceptible to cracking, and the cured coating film has practical adhesion to substrates and coating durability. When forming a cured coating film of the curable artificial nail composition of the present invention, the same equipment as that used when curing a radically polymerizable curable composition, for example, general ultraviolet curing equipment or nail polish curing equipment, can be used.
[0065] The curable artificial nail composition of the present invention can be particularly suitably used as a gel nail. For example, when used to form any of a base coat layer applied directly to the user's nail, a color coat layer applied on the base coat layer, and a top coat layer applied on the base coat layer, the cured coating film will not chip or peel off for a long period of time (for example, at least two weeks after curing), and the occurrence of lifting on the lower layer or the user's nail can be suppressed. When used as a color coat layer, it can be used by using a colorant to tone the color in a variety of ways, such as solid colors, glitter tones, metallic luster tones, dark colors, bright colors, etc. In addition, after applying the curable artificial nail composition of the present invention, small decorations, powders, etc. can be attached to the coating film surface of the curable artificial nail composition before curing to enhance the design. The curable artificial nail composition of the present invention is particularly suitable for use as a base coat layer (gel base; foundation layer) since it has excellent adhesion to nails.
[0066] [Coating nails with a curable artificial nail composition] The nails to be coated with the curable composition of the present invention may be either human fingernails or toenails, or may be the nails of animals such as dogs and cats, etc. Furthermore, they may be artificial nails such as nail tips (false nails). When the curable artificial nail composition of the present invention is applied to a nail or an (un)cured coating film on the nail to form a coating, the applied surface may or may not be sanded. The method for applying the curable artificial nail composition is not particularly limited, and for example, an application method using an applicator such as a brush or an inkjet may be used.
[0067] Using the curable artificial nail composition of the present invention, an uncured coating layer having the shape of a nail or the like can be prepared on at least one surface of a sheet, and this layer can be brought into contact (transferred) with the nail surface, and then cured by irradiating with ultraviolet light, with or without peeling off the sheet. By using a method in which an uncured coating layer is first formed on the sheet surface using a curable artificial nail composition and then this is transferred, it is possible to coat the nail surface with a uniform and accurate pattern without using an applicator such as a brush, and there is no need to wash the applicator after use.
[0068] The means for curing the curable artificial nail composition after application is not particularly limited as long as it is a means capable of imparting energy for causing the curing of the curable artificial nail composition. Examples include irradiation with energy rays such as light (ultraviolet rays (UV) etc.), electron beams, heat etc. In particular, curing by irradiation with ultraviolet rays (UV) is preferably used since it can be carried out relatively quickly and easily. When curing by irradiation with light such as ultraviolet rays, a known ultraviolet curing device is used. Although the amount of energy required for curing differs depending on the composition of the curable artificial nail composition, for example, when curing by irradiation with light such as ultraviolet rays, the irradiation energy (accumulated light amount) by light irradiation is, for example, 5 mJ / cm. 2More than 10 mJ / cm, preferably 10 mJ / cm 2 or more, for example 1000 mJ / cm 2 Less than or equal to 800 mJ / cm 2 If the irradiation energy is within this range, nail art having sufficient adhesion and abrasion resistance can be obtained.
[0069] As a light source for irradiating light, for example, a known ultraviolet light source such as a mercury lamp, a metal halide lamp, an ultraviolet light emitting diode (UV-LED), an ultraviolet laser diode (UV-LD), etc. Among them, from the viewpoints of small size, long life, high efficiency, and low cost, an ultraviolet light emitting diode (UV-LED; wavelength 385 to 415 nm; peak wavelength about 405 nm) and an ultraviolet laser diode (UV-LD) are preferred. EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass."
[0071] [Examples A1 to A14, Examples B1 to B14, Examples C1 to C12] [Comparative Examples A1 to A13, Comparative Examples B1 to B12, Comparative Examples C1 to C14] The components shown in Tables 1 to 6 were placed in a container in the amounts (parts by mass) shown in Tables 1 to 6, and the mixture was heated to 50° C. and stirred with a dissolver. The mixture was defoamed for 10 minutes under a pressure of 0.1 MPa while stirring, and then allowed to stand at 80° C. for 2 hours and defoamed to obtain a curable artificial nail composition. All of these steps were performed in the dark. Examples A1 to A14 and Comparative Examples A1 to A13 are examples and corresponding Comparative Examples in which (Ca) 2-hydroxybutyl (meth)acrylate was used as the (C) (meth)acrylate component. Examples B1 to B14 and Comparative Examples B1 to B12 are examples and corresponding Comparative Examples in which a (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule (Cb) was used as the (meth)acrylate component (C). Examples C1 to C12 and Comparative Examples C1 to C14 are examples and corresponding Comparative Examples in which a (meth)acrylate mixture containing (Cc) a trifunctional or higher polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate was used as the (C) (meth)acrylate component.
[0072] <Ingredients> The components in Tables 1 to 6 are as follows. PUA1: Polycarbonate polyurethane methacrylate (weight average molecular weight 29,000) obtained from hydroxyethyl methacrylate, isophorone diisocyanate and polycarbonate diol. PUA2: Isophorone diisocyanate-polypropylene glycol-hydroxyethyl methacrylate urethane (meth)acrylate (weight average molecular weight 4,000) with two radically polymerizable unsaturated double bonds in one molecule. MA: methacrylic acid AA: Acrylic acid HBMA: 2-Hydroxybutyl methacrylate THFMA: Tetrahydrofurfuryl methacrylate MEDYMA: (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl methacrylate TMPMA: Trimethylolpropane trimethacrylate HEMA: 2-hydroxyethyl methacrylate IBXA: Isobornyl acrylate HPMA: 2-hydroxypropyl methacrylate HEMA: 2-hydroxyethyl methacrylate DMAA: Dimethylacrylamide DEAA: Diethylacrylamide ACMO: Acryloylmorpholine 14DMA: Polyethylene glycol dimethacrylate (-CH2CH2O- repeating units: approx. 14) TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide HCPK: 1-hydroxycyclohexyl phenyl ketone
[0073] <Adhesion evaluation> The obtained curable artificial nail composition was applied onto a nylon plate using a doctor blade to form a coating film with a thickness of 100 μm, and cured by irradiating with a 36 W LED lamp (irradiation wavelength: approximately 385 nm to approximately 415 nm) for 30 seconds. After that, the uncured components were wiped off and removed using an 80 Vol% aqueous ethanol solution to obtain a cured coating film. The cured coating film was cut with a cutter knife into a grid of 25 grids, 6 vertical and 6 horizontal cuts spaced 1 mm apart, reaching the substrate. Cellophane tape (registered trademark, manufactured by Nichiban Co., Ltd.) was applied to the grids, which were then rubbed 10 times with a 500 g weight, and the tape was peeled off at a 45° angle at a constant speed. The adhesion was evaluated according to the following criteria based on the number of squares remaining after peeling, where A is pass and C is fail. The number of squares remaining after peeling and the results of the adhesion evaluation are shown in Tables 1 to 6 as "adhesion." A: 25 squares remained (no peeling). C: Fewer than 25 squares remaining.
[0074] <Water-resistant adhesion evaluation> The obtained curable artificial nail composition was applied onto a nylon plate using a doctor blade to form a coating film with a thickness of 100 μm, and cured by irradiating with a 36 W LED lamp (irradiation wavelength: approximately 385 nm to approximately 415 nm) for 30 seconds. After that, the uncured components were wiped off and removed using an 80 Vol% aqueous ethanol solution to obtain a cured coating film. The cured coating film was cut with a cutter knife into a grid of 25 grids, 6 vertical and 6 horizontal cuts spaced 1 mm apart, reaching the substrate. 0.5 mL of water was dropped onto the grids, left to stand for 10 minutes, then wiped off, and cellophane tape (manufactured by Nichiban Co., Ltd., registered trademark) was applied. The surface was rubbed 10 times with a 500 g weight, and the tape was peeled off at a constant speed at an angle of 45°. The adhesion was evaluated according to the following criteria based on the number of squares remaining after peeling: A is pass, and C is fail. The number of squares remaining after peeling and the results of the water-resistant adhesion evaluation are shown in Tables 1 to 6 as "water-resistant adhesion". A: 25 squares remained (no peeling). C: Fewer than 25 squares remaining.
[0075] <Evaluation of adhesiveness against disinfectant alcohol> The obtained curable artificial nail composition was applied onto a nylon plate using a doctor blade to form a coating film with a thickness of 100 μm, and cured by irradiating with a 36 W LED lamp (irradiation wavelength: approximately 385 nm to approximately 415 nm) for 30 seconds. After that, the uncured components were wiped off and removed using an 80 Vol% aqueous ethanol solution to obtain a cured coating film. The cured coating film was cut with a cutter knife into a grid of 25 grids, 6 vertical and 6 horizontal cuts spaced 1 mm apart, reaching the substrate. 0.5 mL of ethanol for hand disinfection (a mixture of 80% by volume of ethanol and 20% by volume of ion-exchanged water) was dropped onto the grids, left to stand for 10 minutes, then wiped off. Cellophane tape (manufactured by Nichiban Co., Ltd., registered trademark) was then applied, and the surface was rubbed 10 times with a 500 g weight, after which the tape was peeled off at a constant speed at an angle of 45°. The number of squares remaining after peeling was used to evaluate the rubbing alcohol resistance adhesion according to the following criteria: A is pass, and C is fail. The number of squares remaining after peeling and the results of the rubbing alcohol resistance adhesion evaluation are shown in Tables 1 to 6 as "ALC resistance adhesion". A: 25 squares remained (no peeling). C: Fewer than 25 squares remaining.
[0076] <Evaluation of water immersion cloudiness> The obtained curable artificial nail composition was applied onto a polypropylene film using a doctor blade to form a coating film with a thickness of 100 μm, and cured by irradiating with a 36 W LED lamp (irradiation wavelength: approximately 385 nm to approximately 415 nm) for 30 seconds. After that, the uncured components were wiped off and removed using an 80 Vol% aqueous ethanol solution to obtain a cured coating film. A rectangular test piece containing the cured coating was prepared from the polypropylene film on which the cured coating was formed, and after leaving it for 2 hours with part of the cured coating immersed in tap water, it was removed and the water was wiped off, and the state and degree of cloudiness of the cured coating, including the part immersed in tap water, were visually observed, and a water immersion cloudiness resistance evaluation was performed based on the following criteria. A and B are pass, and C to E are fail. The results of the water immersion cloudiness evaluation are shown in Tables 1 to 6 as "cloudiness resistance". A: It is not cloudy. B: Slightly cloudy, but this is not noticeable unless you are at the boundary between the areas immersed in tap water and those not immersed in tap water. C: The area immersed in tap water is cloudy. D: The area immersed in tap water is cloudy and the cured coating film has expanded slightly. E: The area immersed in tap water is completely cloudy and the cured coating film has expanded.
[0077] <Adhesion evaluation> The adhesion of the resulting curable artificial nail composition was evaluated based on the peel-off load. The peel-off load was measured by a 90° peel-off test as follows. The peel-off load thus obtained was used to evaluate adhesion according to the following criteria: A and B are acceptable, and C is unacceptable. The peel-off load values (kg) thus obtained and the results of the adhesion evaluation are shown together in Tables 1 to 4 as "adhesion." A: The 90° peel-off load is 0.4 kg or more. B: The 90° peel-off load is less than 0.4 kg and 0.35 kg or more. C: The 90° peel-off load is less than 0.35 kg.
[0078] (90° peel-off test) The surface of the nylon plate was dried at 50°C for 24 hours or more, and then the surface was wiped with ethanol to remove dirt. The obtained curable artificial nail composition was then cured by irradiating it with a 36 W LED lamp (irradiation wavelength: approximately 385 nm to approximately 415 nm) for 30 seconds. Uncured components were then wiped off with an 80 Vol% aqueous ethanol solution to form a cured coating film 10 mm long and 50 mm wide. The width direction edge of the cured coating film was clamped with a clip attached to a digital force gauge (Imada, ZTA-100N), and the cured coating film was peeled off from the nylon plate in the width direction at a speed of 100 mm / sec at a peel angle of 90°, and the peel-off load (the maximum load (kg) required to peel off the cured coating film) was measured.
[0079] [Table 1]
[0080] [Table 2]
[0081] [Table 3]
[0082] [Table 4]
[0083] [Table 5]
[0084] [Table 6]
[0085] As shown in Tables 1 to 6, the curable artificial nail compositions of Examples A1 to A14, B1 to B14, and C1 to C12 all passed the evaluations of adhesion, water-resistant adhesion, rubbing alcohol-resistant adhesion, and water-immersion-resistant cloudiness. Furthermore, as shown in Tables 1 to 4, the curable artificial nail compositions of Examples A1 to A14 and B1 to B14 all passed the evaluations of adhesion. On the other hand, as shown in Tables 1 to 6, the curable artificial nail compositions of Comparative Examples A1 to A13, B1 to B12, and C1 to C14 all failed the evaluations of adhesion, water-resistant adhesion, rubbing alcohol-resistant adhesion, and water-immersion-resistant cloudiness.
Claims
1. (A) a (meth)acrylate oligomer, (B) (meth)acrylic acid, (C) The following (Ca) to (Cc); (Ca) 2-hydroxybutyl (meth)acrylate, (Cb) a (meth)acrylate compound having a (meth)acryloyloxy group and a heterocycle in the molecule; (Cc) a (meth)acrylate mixture containing a tri- or higher functional polyfunctional (meth)acrylate compound and 2-hydroxyethyl (meth)acrylate, wherein the content of the tri- or higher functional polyfunctional (meth)acrylate compound is 0.01% by mass or more and 5.0% by mass or less relative to 100% by mass of the total amount of the curable artificial nail composition; A (meth)acrylate component comprising one or more selected from the group consisting of: (D) a polymerization initiator, A curable artificial nail composition comprising:
2. The curable artificial nail composition according to claim 1 , further comprising (E) an alicyclic (meth)acrylate compound.
3. 3. The curable artificial nail composition according to claim 1, wherein the (A) (meth)acrylate oligomer is a polycarbonate polyurethane (meth)acrylate oligomer and / or a polyether polyurethane (meth)acrylate oligomer.
Citation Information
Patent Citations
Artificial nail raw material composition, method for curing artificial nail raw material composition, method for producing artificial nail and artificial nail
JP2020132597A
Curable artificial nail composition
JP2022167214A
Photocurable artificial nail composition
WO2015163353A1
Photocurable composition to be used on fingernails or artificial nails, and method for coating by using same
WO2017082058A1
Artificial nail composition improved in adhesivity
JP2010053097A
Cited By
Gel nail application method
JP7737765B1
Gel nail application method
JP7819988B1
